HUBUNGAN ANTARA BEBAN KERJA PERAWAT DENGAN KELENGKAPAN PENDOKUMENTASIAN CATATAN PERKEMBANGAN PASIEN TERINTEGRASI - Ashifa, Nida; Azidin, Yustan; Iswantoro, Iswantoro; Damayanti, Eka; Khalilati, Noor (NHM PRESS, 2024)
Basically, every nurse who will provide nursing services must be responsible and obliged to document the information made, so that the information can be useful for other health workers. The incompleteness of documentation in integrated patient progress records is due to the high workload of nurses. The purpose of the study was to determine the relationship between nurse workload and the completeness of documenting integrated patient progress records in the inpatient of Banjarmasin Islamic Hospital. Research design quantitative correlation of analytical with cross sectional approach. The population of this study was 84 nurses. Sampling is done by probability sampling, which is using simple random sampling. The sample of this study was nurses at Banjarmasin Islamic Hospital Inpatient as many as 69 nurses. Data collection using nurse workload questionnaires and observation of patient progress records were integrated using spearman rank tests. The results of the research test in this study obtained p value (0.001) < α (0.05) so that it can be concluded that there is a significant relationship between the workload of nurses and the completeness of documenting integrated patient progress records in Islamic Hospital Inpatients. Therefore, it is important to carry out teamwork both between nurses or with other health teams in carrying out work in order to maintain the quality of documentation on integrated patient development records.